Estimation of the water footprint of sugarcane production for the mills of the Papaloapan basin - GARAY JACOME, ANGELES SUHGEY (Revista Mexicana de Ciencias Agrícolas, 2022)
In the world and in Mexico, agriculture uses approximately 75% of fresh water. The scarcity of water worldwide forces that water-saving techniques are increasingly used in the agricultural sector, since it has economic value. An important concept that helps to know the amount of water used in production and consumption is the water footprint. The objective of this research is to estimate the water footprint for the cultivation of sugarcane in the Papaloapan basin to propose measures that contribute to improving the efficiency of water use in this crop. For this research, the water footprint of the 12 sugar mills in the Papaloapan region was calculated, it was carried out following the procedure of Allen et al. (2006); FAO (2006); Haro et al. (2014). The largest water footprint is recorded in the areas that supply cane to the sugar mills of El Carmen (328 m3 t-1 of cane), San Nicolás (313 m3 t-1 of cane) and San José de Abajo (309 m 3), while the mill of San Pedro registered the smallest water footprint (239 m3 t-1). Per hectare, the areas that supply cane for El Carmen have the highest value with 21 301 m3, followed by San Nicolás with 21 221 m3 and by San Miguelito with 20 923 m3. In these areas, it is possible to reduce the water footprint by better managing the crop and using varieties with more productivity.
Keywords: huella hídrica; sugarcane; water footprint